On the role of nutrition in physical, psychomotor, and mental development in infants and young children - V. M. Studenikin (Лечащий Врач)
Background. The physical development of a child is in direct dependence on the actual diet, not only quantitative, but also qualitative composition. In addition to indicators such as body weight and length, the correct formation of body composition is important. The influence of nutrition on indicators of neuropsychiatric development is the basis of the concept of neurodietology. To date, it is generally recognized that the amino acid composition of protein, oligosaccharides, omega-3 and omega-6 fatty acids and a number of other nutrients have a positive effect on the development of the central nervous system and its functions.Objective. The paper is dedicated to the role of nutrition in infants and young children.Results. Some nutritional aspects of physical, psychomotor, mental, emotional and cognitive development are mentioned, as determinants of somatic and psychoneurological health in the described period of pediatric age. Further, the schematic description of alimentary physiology and associated development regulation in infants and young children are provided, including brain-gut axis and humoral regulation of feeding behavior. The specifities of contemporary human milk substitutes are considered, and those of goat milk-based formulas in particular. The product line is available in Russia and is exemplified as a demonstration of contemporary infant/child food products for individuals aged from 0 to 3 years, and focused on optimizing the milestones of physical and psychomotor development. The conclusion states that the use of contemporary human milk substitutes and follow-on formulas is aimed at achieving not solely physical developmental ranges (body weight, body length), but at mental, emotional, cognitive developmental skills, and verbal faculties, as well.